2015
DOI: 10.1177/003335491513000311
|View full text |Cite
|
Sign up to set email alerts
|

Using Smartphone Apps in STD Interviews to Find Sexual Partners

Abstract: Objectives. Smartphone applications (apps) are increasingly used to facilitate casual sexual relationships, increasing the risk of sexually transmitted diseases (STDs). In STD investigations, traditional contact elicitation methods can be enhanced with smartphone technology during field interviews.Methods. In 2013, the Monroe County Department of Public Health conducted a large, multi-infection STD investigation among men who have sex with men (MSM) using both index case and cluster interviews. When patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
(12 reference statements)
0
25
0
2
Order By: Relevance
“…Sexual health information and advice is increasingly available online, 26 27 and although our study preceded the widespread use of dating-apps, other studies have explored their potential to be used for STI prevention. For example, among MSM, dating-apps have been shown to enhance partner notification, 28 and it has been suggested that integrating HIV prevention interventions into dating-apps might allow for targeting of individuals who exhibit markers of risk in their individual profiles. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Sexual health information and advice is increasingly available online, 26 27 and although our study preceded the widespread use of dating-apps, other studies have explored their potential to be used for STI prevention. For example, among MSM, dating-apps have been shown to enhance partner notification, 28 and it has been suggested that integrating HIV prevention interventions into dating-apps might allow for targeting of individuals who exhibit markers of risk in their individual profiles. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, apreende-se que os aplicativos móveis podem figurar-se como importantes ferramentas nas estratégias de prevenção as IST/Aids e, consequentemente, à diminuição da vulnerabilidade (16,20) . Através do aplicativo comercialmente utilizado nos Estados Unidos, especificamente na Califórnia e em Los Angeles, é possível recrutar indivíduos para estudos relacionados à prevenção do HIV e desenvolver intervenções exitosas.…”
Section: Discussionunclassified
“…Neste segmento, observam-se os reais benefícios proporcionados pelo uso dos aplicativos de prevenção, porém, estudos ressaltam a necessidade de uma maior divulgação deste serviço, uma vez que os aplicativos de busca por parceiros são mais evidentes e mais utilizados quando comparados aos de intervenção (20,22,(24)(25) .…”
Section: Discussionunclassified
“…Meeting sex and romantic partners through geosocial networking (GSN) apps is common among MSM and poses a challenge to traditional HIV/STD partner notification (Pennise et al, 2015;Phillips et al, 2014;Rice et al, 2012). GSN apps use global positioning system technology on smartphones to allow users to connect with other users based on their location.…”
mentioning
confidence: 99%
“…GSN apps use global positioning system technology on smartphones to allow users to connect with other users based on their location. MSM may communicate with sex partners met through GSN apps solely through the apps and choose not to exchange any other contact information, limiting their own and health departments' ability to notify partners of HIV/STD exposure through standard notification methods (Pennise et al, 2015). Historically, partners have been notified in person or by phone, although many health departments have adapted over time to include notification through email, instant messaging, social networking sites, and sex-seeking sites, and internet partner notification has been found to be acceptable to U.S. MSM (Ehlman et al, 2010;Hunter et al, 2014;Klausner, Wolf, Fischer-Ponce, Zolt, & Katz, 2000;McFarlane, Kachur, Klausner, Roland, & Cohen, 2005;Mimiaga et al, 2008;Udeagu et al, 2014;Vest, Valadez, Hanner, Lee, & Harris, 2007).…”
mentioning
confidence: 99%